EVALUASI KURIKULUM PRODI PAI STAI AL-QOLAM MELALUI ANALISIS KORELASI PEMBERLAKUAN MATA KULIAH PRASYARAT TERHADAP PRESTASI AKADEMIK MAHASISWA DALAM MATA KULIAH MICRO TEACHING - Abdurrahman., S.HI., M.Pd (El-QUDWAH, 2014)
Oleh: Abdurrahman Dosen STAI Al-Qolam Gondanglegi Malang Email: abdurrahman@staialqolam.com   Abstract This study started from the search effort a correlation between several courses prerequisite to the particular course which shows the four principles of employment in the curriculum construction: scope, sequence, continuity, articulation and balance. Where the results of this effort will be one important ingredient in the evaluation of curriculum construction in STAI Al-Qolam Gondanglegi, especially on Islamic education faculty (Prodi PAI) with CIPPevaluation model. As the beginning research hypothesis, that there is a strong correlation between the eight independent variables on the dependent variable, is a manifestation of the presence of internalized motivation. This study uses a Secondary Data Analysis (SDA) with purposive sampling technique, that is a complete transcript of PAI students in 2009. Calculation result by SPSS, and by considering three important assumption: autocorrelation, multicollinearity, and heteroscedasticity, which shows that the output obtained 8 independent variable has a strong correlation to the dependent variable. Obtained figures of significance p = 0.000 0.01, which means the eighth prerequisite subjects have donated considerable influence: 90.6%, of the results of student performance on Micro Teaching courses.